Die Vielen Leben des Arkan
This broadcast profiles Zeljko Raznatovic Arkan, notorious leader of the Tigers, a Serbian paramilitary unit. His life is briefly chronicled from his rise as a gangster, wanted by Interpol in many Western European countries, to his activities in the war in the former Yugoslavia as a top paramilitary leader. Arkan's exploits as head of Red Star's fan club are detailed, showing how he was able to recruit individuals from the fan club for his paramilitary units. Arkan's ascent into Serbian politics as a parliamentary representative of Kosovo is also explored. Professor Vladan Vasilijevic describes how Arkan represents a pattern in Serbia since the break up of the former Yugoslavia, "the criminalization of politics and the politicization of criminal activity."